102k views
4 votes
Solve for x step by step 2x - 3 > 2x-5/2

User NicolasZ
by
5.4k points

1 Answer

4 votes

Answer: x= -1

2x + 3(5 - x) - 12 = 4(x + 2)

1) pass: Delete the parentheses, making the multiplications.

2x + 15 - 3x - 12 = 4x + 8

2) pass: Put the numbers with incognito on the left and change the signal when changing sides if necessary, put the numbers without incognito on the right by changing the signal if necessary.

2x + 15 - 3x - 12 = 4x + 8

2x - 3x - 4x = - 15 + 12 + 8

3) pass: Solve the equations not forgetting the signal rules.

2x - 3x - 4x = - 15 + 12 + 8

- x - 4x = - 3 + 8

- 5x = 5 Simplify by (-1) Exchanging the signals

5x = -5

User Andriy Tylychko
by
5.3k points